Efficient Perovskite Light‐Emitting Diodes via Tuning Nanoplatelet Distribution and Crystallinity Orientation. Issue 20 (20th August 2018) - Zou, Yatao; Huang, Qi; Yang, Yingguo; Ban, Muyang; Li, Siying; Han, Yujie; Wu, Tian; Tan, Yeshu; Gao, Xingyu; Song, Tao; Sun, Baoquan
Abstract: Quasi‐2D Ruddlesden–Popper (RP) perovskites with quantum‐size‐tuned nanoplatelet crystallites are particularly attractive for light‐emitting diode (LED) applications because of their excellent charge transport, bandgap tunability, and narrow emission peaks. Favorable energy cascade structure in 2D RP perovskites can funnel the photoexcitation from large‐bandgap nanoplatelets to the lowest bandgap ones, which promises efficient radiative recombination. However, how to rationally control the nanoplatelet distribution as well as the crystallization characteristics to ensure efficient energy transfer and charge transport in perovskite films is still challenging. Here, a simple path to facilely tune the nanoplatelet distribution as well as the crystal orientation via carefully controlling postannealing condition is provided. With optimizing the thermal annealing time, compact and flat perovskite films with high photoluminescence quantum yield are obtained. Based on the optimized perovskite films, green LED with a current efficiency of 43.7 cd A −1, corresponding to an external quantum efficiency of 13.9%, is achieved. This work provides a simple path to target highly efficient perovskite LED devices. Abstract : Efficient perovskite light‐emitting diodes (LEDs) are achieved via tuning nanoplatelet distribution and the crystallinity orientation of quasi‐2D perovskite films. By using the optimized perovskite film to build LED devices, a current efficiency of 43.7 cd A −1 and an external quantum efficiency of 13.9% are achieved, which are the one of the impressive performances in this field.